Geotechnical Behaviour of a Malaysian Residual Granite Soil - Taha, Mohd Raihan; Hossain, Md.kamal; Chik, Zamri; Mohd Nayan, Kahirul Anuar (Universiti Putra Malaysia Press, 1999)
Granite soil is widely distributed in Peninsular Malaysia. Steep terrain, heavy seasonal rainfall and deep tropical weathering are the main causes of numerous slope failures in this formation. Information on the shear strength of soil and its behaviour is essential for safe and economic design geotechnical structures. In order to study the fundamental behaviour of this residual soil, direct shear tests were conducted on remoulded and undisturbed specimens. The soil was subjected to soaked and unsoaked conditions to study the effects of wetting. In addition, triaxial CD and C tests were also conducted. The behaviour in direct and triaxial shear did not indicate peak strength in the stress-strain plots in all specimens. In direct shear tests, significant volume change behaviour was observed between unsoaked and soaked specimens. The shear strengths of soaked specimens were significantly lower than that of unsoaked specimens. Thus the effects of wetting is very obvious. In triaxial tests, the strength parameters (c', tP') for CD and CD tests were not found similar. All important observations are highligted in the paper.